Suicide and socio-economic indicators : What are the missing links? - Tan, Sandra Chia Chia (Universiti Malaysia Sarawak (UNIMAS), 2012)
The purpose of this study is to examine the relationship between suicide and socioeconomic indicators in Canada. Annual data from 1970 to 2008 was utilized in the analysis for number of suicides for male (LTOM), number of suicides for female (LTOF), unemployment rate (UNEM), real gross domestic product per capita (LRGDPPC), total fertility rate (LFER), female labour participation rate (FLPR), total numbers of crime (LCRIME) and alcohol consumption per capita (LALC). In this study, various tests namely lohansen-luselius cointegration test, vector error correction model (VECM) Ganger causality test, vector autoregressive model (VAR) Granger causality test and variance decomposition (VDCs) were used. VDCs are employed after the causality tests in VECM and V AR framework. The results from VDCs support the causality results in this study. It is noted that UNEM, LRGDPPC and LFER are found as leading variables in the system among four socio-economic indicators for L TOF and L TOM in the five models. In 50-year horizon, these three variables will affect the suicide rates for both genders.